Financial Literacy Development On Housewives As A Basis For Building Family Financial Resilience - Hikmah; Dian Efriyenti; Khadijah Khadijah (MOVE: Journal of Community Service and Engagement, 2022)
The implementation of community service activities that will be carried out in the form of Financial Literacy Development for Housewives as a Basis for Building Family Financial Resilience in Barelang Mega Jaya Sejati Housing. The number of problems that have been encountered, the performance of a woman is at stake because she is required to harmonize and regulate the amount of income and increase in some basic necessities and daily needs. In addition to problems regarding financial management and lack of understanding of financial literacy, the problem that the service wants to minimize is related to the lack of knowledge of housewives related to fintech. This service will be carried out for 5 meetings with the material for each meeting will be different to solve existing problems. The methods provided during this service are lectures, tutorials and exercises related to financial literacy. Barelang Mega Jaya Sejati housewives already have an understanding of the importance of financial education in managing household finances so that the planning can run smoothly.